Increasing Financial Management Competency Through Basic Accounting Training for Small and Medium Enterprises in Malaysia - Meutia , Inten; Yusrianti, Hasni; Novriansa , Agil; Yaacob, Zulnaidi (Pascasarjana Universitas Mataram, 2025)
Financial management issues are inextricably linked to the growth of SMEs since effective financial management necessitates accounting knowledge, which not all SMEs possess. This is because human resources lack the skills and knowledge necessary for effective business management. The goal of financial management training is to assist SMEs in figuring out the best selling price for their goods and in improving and streamlining the management of basic financial reports for companies they have operated by moving from manual to digital models. The first steps of the training process involve teaching participants the value of financial reports and how to create basic financial reports. Strategies for figuring out selling prices for the goods being sold are explained and helped with. Thirty small and medium-sized businesses (SMEs) in Balik Pulau, Penang, Malaysia, received this training and mentoring